(untitled) (GESTIÓN Y TENDENCIAS, 2020)
Digital Transformation (DT) has been characterized as a process of profound change aimed at improving organizations, the delivery of products and services, and the experience of those who access them, thanks to the use of available digital technologies. In Chile, the recently enacted Digital Transformation Act establishes a strong link between DT and Electronic Records Management (ERM), promoting a shift within the State from paper-based to fully digital management. ERM nevertheless rests on a series of prior standards and processes that are technologically agnostic and that should be taken into account in order to ensure the success of DT and the effective use of current technologies for managing information within organizations.